Intestinal parasites of Myocastor coypus(Rodentia, Myocastoridae) on animal farms inEastern Ukraine - Sumakova, N. V.; Сумакова, Н. В.; Paliy, A. P.; Палій, А. П.; Pavlichenko, O. V.; Павліченко, О. В.; Petrov, R. V.; Петров, Р. В.; Morozov, B. S.; Морозов, Б. С.; Plys, V. M.; Plys, V.; et al. (Oles Honchar Dnipropetrovsk National University, 2025)
Keeping and breeding of nutria Myocastor coypus (Molina, 1782) (Rodentia, Myocastoridae) is gaining popularity due to the biological characteristics of these animals and their undemanding habitat conditions. The study aimed to investigate the parasitofauna of nutria depending on the technology of their keeping under the conditions of fur farms in Eastern Ukraine (Kharkiv region). Fecal samples of 377 animals of different age and sex groups from farms in various districts of the Kharkiv region under aviary and cage conditions were examined. In addition, 30 samples of 10 g each from nutria carcasses (tongue, masticatory muscle, diaphragm) were analyzed for trichinosis. It was found that the infe c tion rate of nutria o n the farms of the Kharkiv region was, on average, 40.3% of the examined animals. The average infection rate in caged nutria is 36.7%, and in aviary breeding, 44.1%. The predominant endoparasites of nutria in the Kharkiv region are protozoa (28.4%), with a slightly lower percentage (8.2%) of helminths. Mixed infection of animals is noted in 3.7%. The detected parasitic agents belong to the classes Nematoda (Enoplea) Rudolphi, 1808, and Sporozoa Levine, 1970. Eimeria myopotami Yukimoff, 1933 (Eucoccidiorida, Eimeriidae) and Strongyloides myopotami Artigas et Pacheco, 1933 (Rhabditida, Strongyloididae) were found to be the most common parasites in the nutria. The prev a lence of simultaneous infection with three pathogens ( Trichuris myocastoris Enigk, 1933 (Trichocephalida, Trichur i dae), Strongyloides myopotami , Eimeria myopotami ) was 8.7% in the aviary farm and 4.8% in the cage farm. The lo w est prevalence of helminth infection in nutria was observed in animals aged 1 – 2 months (2.1%), and the highest prev a lence of mixed infection was observed in nutria aged 6 – 8 months (9.2%). In aviary housing, Eimeria infection of nutria was observed throughout the year, with no worm infection in December and no mixed infection in February, May through October, and November. In cage housing, Eimeria infection was absent in January, and worm infection was absent in March, May through September, and December. Mixed infections were detected in January, April, and Se p tember, mainly in young females. Pathogens Cryptosporidium spp. Tyzzer, 1907 (Eucoccidiorida, Cryptosporidiidae) and Giardia spp. Künstler, 1882 (Diplomonadida, Hexamitidae) were not found in nutria. Testing for trichinosis was negative. Prospects for further research include the development of modern, science-based measures for the prevention and control of parasitic diseases in commercial animals. Утримання та розведення нутрій Myocastor coypus (Molina, 1782) (Rodentia, Myocastoridae) набуває популярності завдяки біологічним особливостям цих тварин та їх невибагливим умовам існування. Метою дослідження було вивчення паразитофауни нутрій залежно від технології їх утримання в умовах звіроферм Східної України (Харківська область). Були досліджені зразки фекалій 377 тварин різних вікових та статевих груп з ферм різних районів Харківської області в вольєрних та кліткових умовах. Крім того, було проаналізовано 30 зразків по 10 г кожен з туш нутрій (язик, жувальний м'яз, діафрагма) на трихінельоз. Було виявлено, що рівень зараженості нутріями на фермах Харківської області становив у середньому 40,3% від обстежених тварин. Середній рівень зараженості в клітковому утриманні нутрій становить 36,7%, а у вольєрному розведенні - 44,1%. Серед ендопаразитів нутрій Харківської області переважають найпростіші (28,4%), дещо менший відсоток (8,2%) гельмінти. Мікст-інфекція тварин відзначається у 3,7%. Виявлені паразити належать до класів Nematoda (Enoplea) Rudolphi, 1808 та Sporozoa Levine, 1970. Eimeria myopotami Yukimoff, 1933 (Eucoccidiorida, Eimeriidae) та Strongyloides myopotami Artigas et Pacheco, 1933 (Rhabditida, Strongyloididae) виявлено, що вони є найпоширенішими паразитами у нутрій. Поширеність одночасного інфікування трьома збудниками (Trichuris myocastoris Enigk, 1933 (Trichocephalida, Trichuridae), Strongyloides myopotami, Eimeria myopotami) становила 8,7% на вольєрній фермі та 4,8% на клітковій фермі. Найнижча поширеність гельмінтозної інфекції у нутрій спостерігалася у тварин віком 1-2 місяці (2,1%), а найвища поширеність змішаної інфекції спостерігалася у нутрій віком 6-8 місяців (9,2%). У вольєрному утриманні інфекція нутрій еймерією спостерігалася протягом усього року, без глистяної інфекції у грудні та змішаної інфекції у лютому, з травня по жовтень та листопаді. У клітковому утриманні інфекція еймерією була відсутня у січні, а глистяна інфекція була відсутня у березні, з травня по вересень та грудні. Змішані інфекції виявлялися у січні, квітні та вересні, переважно у молодих самок. Патогени Cryptosporidium spp. Tyzzer, 1907 (Eucoccidiorida, Cryptosporidiidae) та Giardia spp. Künstler, 1882 (Diplomonadida, Hexamitidae) у нутрій не були виявлені. Результати тестування на трихінельоз були негативними. Перспективи подальших досліджень включають розробку сучасних, науково обґрунтованих заходів для профілактики та контролю паразитарних захворювань у промислових тварин.
Кишкові паразити Myocastor coypus (Rodentia, Myocastoridae) на тваринницьких фермах Східної України
Плис В'ячеслав Миколайович https://orcid.org/0000-0002-9984-4048
Keywords: Protozoa; найпростіші; nutria; нутрії; keeping technology; технологія утримання; parasitic diseases; паразитарні хвороби; helminths; гельмінти